Rude Boy Subculture, Critical Pedagogy, and the Collaborative Construction of an Analytic and Evocative Autoethnography. (February 2016) - Williams, J. Patrick; Jauhari bin Zaini, Muhammad Kamal
This article theorizes and performs an analytic and evocative autoethnography about participation in the Rude Boy subculture in Singapore in the 2000s. Relying on critical pedagogy and a performative conception of subcultural theory, we analyze the second author's past self as a Rude Boy through a collaborative narrative that emerged out of a university course–based research project on youth subcultures. Our narrative, which includes the reproduction of field notes, reflective journals, interviews, and dialogue between the authors, is intended to simultaneously question the assumed dichotomy between analytic and evocative autoethnographic forms and to highlight the potential for a critical pedagogy that brings teachers and students together to create new understandings of the self. The article also highlights the personal and pedagogical outcomes of dealing academically with a subcultural past and extends a dialogic approach to studying subcultural participation and experience.